Psikologi Tasawuf: Personaliti Sufi Menurut Kitab al-Hikam Ibnu Athaillah: The Psychology of Sufism: Sufi Personality According to al-Hikam by Ibn Athaillah - Nasution, Saipul Anwar (Jurnal Usuluddin, 2023)
This article specifically analyzes the book al-Hikam regarding sufi personalities and their differences compared to personalities according to psychology. The focus of the psychological study aligns with sufism in terms of the soul and its behaviors, however sufism takes a step further by encompassing studies related to the essence of the spirit. From the epistemological perspective, psychology is centered on the investigation of mental problems including personality disorders and mental illnesses. Meanwhile, sufism solely discusses about the heart, the process of purifying the heart, recognizing Allah, and the development of human character and soul. The background of the article is to seek solutions to contemporary 'mental issues' where the psychotherapeutic methods utilized by psychologists have not been entirely successful in dealing with mental health problems. Hence, the knowledge of Sufism is considered as an alternative to psychotherapeutic methods. Additionally, an individual's personality also shapes their future. In psychology, personality refers to a person's character or behavior when coping with situations in life and finding solutions. The question addressed in this study is how an individual's personality influenced by sufi elements can empower their own personality. Moreover, the prominence of Ibn Ataillah and his magnum opus, al-Hikam which makes a substantial positive impact on the development of personality.